Can the same controlled attenuation parameter cut-offs be used for M and XL probes for diagnosing hepatic steatosis? - Chan, Wah Kheong; Nik Mustapha, Nik Raihan; Mahadeva, Sanjiv; Wong, Vincent Wai-Sun; Cheng, Jenny Yeuk-Ki; Wong, Grace Lai-Hung (Wiley, 2018)
Background and Aim: There are limited studies on controlled attenuation parameter (CAP) using Fibroscan XL probe for the diagnosis of hepatic steatosis grade. The aim of this study was to determine whether previously defined optimal cut-offs for CAP using the M probe could be applied for the XL probe. Methods: Adult patients with chronic liver disease who had a liver biopsy and examination with both the M and XL probes were included. Previously defined optimal cut-offs for CAP using the M probe were used for the diagnosis of steatosis grades ≥S1, ≥S2, and S3 (248, 268, and 280 dB/m, respectively). Results: Data for 180 patients were analyzed (mean age 53.7 ± 10.8 years; central obesity 84.5%; non-alcoholic fatty liver disease 86.7%). The distribution of steatosis grades was S0, 9.4%; S1, 28.3%; S2, 43.9%, and S3, 18.3%. The sensitivity, specificity, positive predictive value, and negative predictive value of CAP using the M/XL probe for the diagnosis of steatosis grade ≥S1 was 93.9%/93.3%, 58.8%/58.8%, 95.6%/95.6%, and 50.0%/47.6%, respectively. These values were 94.6%/94.6%, 41.2%/44.1%, 72.6%/73.6%, and 82.4%/83.3%, respectively, for ≥S2, and 87.9%/87.9%, 27.2%/27.9%, 21.3%/21.5%, and 90.9%/91.1%, respectively, for S3. Conclusion: The same cut-off values for CAP may be used for the M and XL probes for the diagnosis of hepatic steatosis grade.